Dear Teacher : Expert Advice for Effective Study Skills. - Peltz, William H. (SAGE Publications, 2007)
Addresses common defense mechanisms and rationalizations students use to avoid studying, and offers ready-to-use and easy-to-understand skills for middle and high school classrooms.